2003
DOI: 10.1023/a:1025438223608
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness accuracy rates in police showup and lineup presentations: A meta-analytic comparison.

Abstract: Meta-analysis is used to compare identification accuracy rates in showups and lineups. Eight papers were located, providing 12 tests of the hypothesis and including 3013 participants. Results indicate that showups generate lower choosing rates than lineups. In target present conditions, showups and lineups yield approximately equal hit rates, and in target absent conditions, showups produce a significantly higher level of correct rejections. False identification rates are approximately equal in showups and lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
159
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 23 publications
10
159
1
2
Order By: Relevance
“…A metaanalysis of earlier research found that the rate of selection is lower in showups than in lineups, but result in similar rates of correct identifications in culprit-present trials (Steblay et al, 2003). Collapsed across Experiments 1-3 the results are consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…A metaanalysis of earlier research found that the rate of selection is lower in showups than in lineups, but result in similar rates of correct identifications in culprit-present trials (Steblay et al, 2003). Collapsed across Experiments 1-3 the results are consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 61%
“…The data suggest that identification is more effective from a video identification procedure, whether it is a showup or a lineup, than from a live showup. In contrast, previous research has found that correct culprit-present identification rates in showups and lineups are similar (Steblay et al, 2003). However, in most of the previous research, photograph showups and photograph lineups have been used.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations